A Comparison of Two Intervention Strategies on the Academic Performance of Student-Athletes - Terry, Lawrence R.; DeGroot, William; O'Brien, Dennis; Campbell, Caroline; Hollstein, Ulrich (My University, 1991)
The purpose of this study was to determine the effect of the Model Student Tutor Program (MSTP) when compared with the traditional study table on the academic performance of football players at the University of Wisconsin-LaCrosse as measured by grades acquired in selected courses. The subjects for this study consisted of eighty-one football players from a Division Ill program, the University of Wisconsin-La Crosse, in the fall semester of 1989. Participants registered in Biology 100 were randomly assigned to one of three groups: one group receiving peer tutoring, one group assigned to the traditional study table, and a control group. Participants registered in 100 level English and history were randomly assigned to one of three groups: one group receiving peer tutoring, one group assigned to the traditional study table, and a control group. Neither of the control groups received the academic intervention. ACT (composite, English, and science) scores were tested for pre-disposing differences. Three hypotheses were developed. The first hypothesis stated that there will be no significant difference in the grades of football players based on the type of intervention for literature-based courses. The second hypothesis stated that there will be no significant difference in the grades of football players, based on the type of intervention for science-based courses. The third hypothesis stated that there will be no significant difference in the grades of football players based on the type of intervention used across course content. Based on the results of an ANOVA, the first hypothesis was rejected while the second and third hypotheses were retained. There was a significant difference between the study table and control group for literature courses. Neither peer tutoring nor study table was significantly effective in improving the performance of football players in science-based classes. It could not be shown that study table or peer tutoring would be more effective if one had to choose between interventions regardless of course content.
Keywords: Division III; academic support; study hall; football